IRS-1 genetic polymorphism (r.2963G>A) in type 2 diabetes mellitus patients associated with insulin resistance - Yousef, Anas; Behiry, Eman; Abd Allah, Wafaa; Hussien, Ahmed; Abdelmoneam, Abdelmoneam; Imam, Mahmoud; Hikal, Doaa (Application of clinical genetics, 2018)
Insulin receptor substrate (IRS) molecules are key mediators in insulin signaling. Several polymorphisms in the IRS genes have been identified, but only the Gly to Arg 972 substitution of IRS-1 seems to have a pathogenic role in the development of type 2 diabetes mellitus (T2DM). Many polymorphisms described in IRS-1 gene, especially Gly972Arg substitution, are shown to be associated with insulin resistance (IR) in T2DM. This prospective case-control study was performed during the period from November 2014 to May 2015. All patients were selected from the Department of Internal Medicine and were screened for eligibility for this study. Subjects were divided into two groups: first group consisted of 100 T2DM patients; second group consisted of 120 nondiabetic controls. First group was further divided into two subgroups: 66 IR patients and 34 insulin-sensitive (IS) patients (homeostatic model assessment [HOMA] was performed). Restriction fragment length polymorphism (RFLP) was performed using specific primers for scanning single-nucleotide polymorphisms (SNPs) such as Gly972Arg (rs1801278 SNP). Taking GG genotype and G allele as references, GA, GA+AA genotypes and A allele showed significantly higher frequency in the T2DM group when compared to the control group, with higher risk to develop T2DM in healthy controls. Taking GG as a reference, rs1801278GA+AA genotype and A allele showed significantly higher proportion in IR when compared to IS, with higher risk to develop IR in T2DM patients. Logistic regression analysis showed that higher FBG, fasting plasma insulin (FPI), HOMA-IR, GA+AA genotypes were associated with higher risk to develop IR in univariable analysis. IRS-1 genetic factor may be a significant genetic determinant for IR in T2DM patients during severe/acute-phase hyperglycemia.